Assessing Doctoral Candidacy: The Development of an Assessment Tool for Comprehensive Portfolios - Freer, John (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
This article presents an assessment tool for doctoral students preparing their comprehensive portfolio. This tool was created from my firsthand experience in the Joint PhD program in Educational Studies—a collaboration between three universities in Ontario, Canada: Lakehead University, Brock University, and the University of Windsor. Following the three criteria for evaluation of the comprehensive portfolio in the program handbook, I developed nine sub-criteria (three for each criterion). This assessment tool can be used for educational purposes, as doctoral students begin to organize and narrate their doctoral journey. Students can map their experiences to the sub-criteria developed, allowing them to be explicit about how their presented scholarly tasks have helped in preparing them for candidacy. While this tool has an obvious application for students within the Joint PhD program, students in other programs with similar requirements may also find it useful due to its theoretical grounding in literature on the process of scholarship.